TINDAK TUTUR ILOKUSI DALAM TRADISI NYESER SAMPER MASYARAKAT DAYAK TABA DI DESA MENYABO - Santi Sari; Patriantoro Patriantoro; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The illocutionary act in the Nyeser Samper Tradition of the Dayak Taba community is a pragmatic study. In this study the authors examined speech acts in the Nyeser Samper Tradition of the Dayak Taba Community in Menyabo Village. In particular, he examines illocutionary illocutionary acts which consist of assertive illocutionary, directive illocutionary, commissive illocutionary, expressive illocutionary and declarative illocution. This study aims to describe the analysis of illocutionary acts in the Nyeser Samper tradition. Descriptive research method with qualitative form. Sources of research data are the Nyeser Samper Tradition, and the local languagespeaking community. Data collection techniques, advanced techniques, documentation techniques, and recording techniques. The tools used, voice recorders, and questionnaires. The results of data analysis in this study, there are eighty illocutionary speeches which include: first, assertive illocutionary speeches containing forty-three utterances. Second, the directive illocution contains twentyone sayings. Third, the commissive illocution has three sayings. The four expressive acts consist of nine utterances. Fifth, there are four declarative focuses. Keywords: Speech Acts, Illocution, Nyeser Samper